Celebrating the 25th Anniversary of UNCLOS Legal Perspective: The Natuna Case - Agusman, Damos Dumoli; Fatihah, Citra Yuda Nur (Indonesian Journal of International Law, 2020)
The 25th Anniversary of UNCLOS was commemorated in early February in Jakarta, just one month after the Chinese fishing vessels and coast guard entered the Indonesia’s EEZ and exploited its natural resources. From the Indonesian side, this China’s encounter has indeed violated the Indonesia’s sovereign rights over its EEZ as well as the breach of Indonesia’s sovereignty by undermining and intervening in Indonesia’s right under international law in exercising legal enforcement in its own jurisdiction. Moreover, the Indonesian government has consistently and persistently rejected the nine-dash line claims by sending official protests through diplomatic notes. The protest also exerts Indonesia’s firm and clear position that Indonesia is not a claimant state to either the sovereignty or territorial disputes in the South China Sea, and therefore will not engage in any negotiation. Furthermore, Indonesia would never recognize the nine-dash line claim since it does not have a legal basis recognized by international law. In contrast, the Indonesia’s sovereign rights are guaranteed by the UNCLOS, as the Indonesia’s EEZ had been acknowledged and registered under the UNCLOS. At the same time, Indonesia will be increasing the frequency of patrols in Natuna waters, and fisheries activities as it is Indonesia’s rights. This Article attempts to identify and describe the Writers’ views over the Natuna case from the legal perspective. The responses of the Indonesian government against the claim are also briefly discussed.